IGF-I and IGF Binding Proteins 2005
DOI: 10.1159/000085755
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I and Risk of Type 2 Diabetes and Coronary Heart Disease: Molecular Epidemiology

Abstract: Insulin-like growth factors (IGFs) play a fundamental role in somatic growth and cellular differentiation, metabolism and survival. Indeed, the processes linking nutrition, metabolism and growth are thought to involve a complex interrelation among insulin, growth hormone (GH), IGFs and their binding proteins (IGFBPs). However, accumulating data from both experimental and molecular epidemiological studies indicate that these growth factors may also be important in the pathophysiological processes underlying chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…A number of epidemiological studies have suggested that IGF-I levels in the lower normal range are associated with an increased risk of ischemic heart disease, stroke, hypertension, reduced glucose tolerance, and diabetes (II, [21][22][23][24]. Although the relationship between IGF-I and cardiovascular disease is still unknown, a protective role in the development of atherosclerosis was suggested for free IGFI levels (24).…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiological studies have suggested that IGF-I levels in the lower normal range are associated with an increased risk of ischemic heart disease, stroke, hypertension, reduced glucose tolerance, and diabetes (II, [21][22][23][24]. Although the relationship between IGF-I and cardiovascular disease is still unknown, a protective role in the development of atherosclerosis was suggested for free IGFI levels (24).…”
Section: Discussionmentioning
confidence: 99%
“…47 Recent prospective epidemiological studies suggest that relatively higher IGF-I levels may reduce the risk of type 2 diabetes and CHD. 48 Increasing evidence indicates, instead, that IGF-1 protects against endothelial dysfunction, an initial step in the development of atherosclerotic lesions, through activation of a suicidal pathway that leads to endothelial cell apoptosis. 49,50 IGF-1 can directly oppose endothelial dysfunction in a number of ways: by interacting with high-affinity endothelial binding sites that lead to nitric oxide (NO) production, 51 by promoting insulin sensitivity 52 and potassium-channel opening, 53 and by preventing postprandial dyslipidemia.…”
Section: Igf Pathway In Cancer and Vascular Diseasementioning
confidence: 99%
“…There is increasing evidence that IGF1 has a protective effect against metabolic syndrome, endothelial dysfunction, atherosclerotic plaque development, and ischemic myocardial damage . There are studies that indicate that high plasma levels of IGF1 may reduce risk of type 2 diabetes and coronary disease [Sandhu, 2005]. Puglielli [2008] concluded that the IGF1 pathway and the IGF1 receptor were involved in the progressive loss of neurogenic capacity in the ageing brain and to the pathogenesis of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%